AN INVESTIGATION OF UNDERGRADUATE SUDENTS’ FILLER TYPE IN ACADEMIC SPEAKING PRESENTATION - Dahlia; Nasori Efendi; Natalia Anggrarini (National Conference on Language, Education, and Technology Proceeding, 2023)
This study aims to investigate the types of fillers used by students during academic speakingpresentations. This qualitative descriptive study used a case study research design to twenty-onestudents of Fourth Semester from English Education Department Wiralodra University whopresented journal topics in academic speaking courses. The instruments used in this study wereobservation and interviews. The data shows that the filler used by students is 7 Lexicalized Fillers(well, and then, like, you know, I think, so and ok) 3 Unlexicalized Fillers (uhh, uhm, and a).Lexicalized fillers are more often used by students during academic speaking presentations,appearing 152 times or 39.07% in 3 unlexicalized fillers, while unlexicalized fillers appear 237 timesor 60.93%. Observations are used to find out what types of filler often appear during studentpresentations. From the students' observations, it is found that many participants used fillers duringpauses and thought of the next word to say, so that fillers could appear. In addition, the researcherfound that the participants often used blank pauses in the middle of the presentation because theydiverted the meaning from the presentation. This study suggested the investigation of the fillerfunction in academic speaking presentation for further research.